Zero-carbon building materials in New Zealand context: a systematic literature review - Ali Hashemi Araghi; Eziaku Onyeizu Rasheed; V. Vishnupriya; Jeff Seadon (Discover Applied Sciences)
Abstract The transition towards zero-carbon building materials represents a critical pathway for mitigating carbon emissions in the construction sector. Utilising recycled materials in construction offers many benefits, most of which are resource conservation. This natural resource conservation helps mitigate environmental degradation and preserve delicate ecosystems. As such, this study aimed to identify the most suitable zero-carbon construction materials for use within New Zealand's building sector by systematically reviewing the literature focusing on wood, rammed earth and strawbale materials. To explore the effectiveness of each material, six primary factors have been identified such as sustainability, cost-efficiency, longevity, visual attractiveness, energy conservation, and ecological ramifications. Therefore, 1808 studies were found on Scopus, IEEE, and Google Scholar. Based on the inclusion and exclusion criteria in this study, the final 20 eligible studies published from 1999 to 2024 were reviewed. This study followed the PRISMA Statement to comprehensively explore the existing literature. Results highlighted that environmental factors such as moisture can directly influence the durability of these construction materials and structures. Although sustainability is often defined in terms of thermal behaviour and life cycle assessment, limited research addresses the aesthetic aspects and comprehensive economic implications of material choices. The findings demonstrate sufficient thermal properties of straw bales and the lower embodied energy of rammed earth compared to other traditional materials, emphasising their potential to enhance energy efficiency in construction. This study recommended future research, contributing valuable insights for stakeholders seeking eco-friendly building components in sustainable construction practices.